Sexual pain disorders among Malay women with type 2 diabetes mellitus in Malaysia - Ismail, Adibah Hanim; Baw, Rawa; Sidi, Hatta; Ng, Chong Guan (ASEAN Federation for Psychiatry and Mental Health, 2014)
Objectives: This study aims to determine the prevalence and associated factors of sexual pain disorders among Malay women in Malaysia with type 2 diabetes mellitus. Methods: This is a cross-sectional study involving 347 women (174 nondiabetic and 173 diabetic subjects) who attended the diabetic clinic in a university hospital. Sexual pain disorders were assessed using the Pain sub scale of Malay Version of the Female Sexual Function Index (MVFSFI). Sociodemographic information of the subjects was collected with a pre-designed questionnaire. Results: Prevalence of sexual pain disorders among Malay women with type 2 diabetes mellitus was 10.4% and the control group was 9.2% but the difference was not statistically significant (p > 0.05). Multivariate logistic regression analysis did not find any relevant associated factor with sexual pain disorder. Conclusion: Sexual pain disorders among Malay women were not dependent on the diabetic status. Further studies with different population of diabetic patients are needed to confirm the results.